A New Methodology for Characterizing the Progressive BD of Hfo2/Sio2 Metal Gate Stacks - Pagano, Roberto (2008)
Dielectric breakdown (BD) of nFETs with TiN metal gates and HfO2 / interfacial layer with 1.09 nm EOT is studied. Occurrence of progressive BD at low current levels is demonstrated. A new measurement methodology for the characteristic growth time and its dependence on gate voltage are reported.2 / interfacial layer with 1.09 nm EOT is studied. Occurrence of progressive BD at low current levels is demonstrated. A new measurement methodology for the characteristic growth time and its dependence on gate voltage are reported.